Mewujudkan Manajemen Zakat yang Modern dan Profesional - -, Mulkanasir (EMPATI: Jurnal Ilmu Kesejahteraan Sosial, 2013)
Muslims in Indonesia have huge potentials, because many of them  are highly-educated, have intellectual predicates and strong economic potentials. This gives a strong potential opportunities for the realization of a very high community, joined in a more specialized institutions in the management of zakah. The fact shows that instead of utilizing zakah properly, many muslims in Indonesia are trying to manage it with great enthusiasm but in perfunctory ways. Such way is really less commendable. In this kind of advanced-era, zakah management model has to be managed in a modern and professional way, so that Muslim community can build a reliable charity civilization and have reliable capability, accountability, and commendable as well. To achieve this aims, we need some consistent efforts regarding to the principles, vision, mission, objectives, planning, hiring models, and financial management transparancy. It is also necessary to integrate the spiritual management of modern management, in order to produce outstanding results and to reach desired target.Keywords : zakat, pengelolaan, manajemen, modern, profesional dan spiritual.